What a digital library of Malay manuscripts should support an exploratory needs analysis - Zainab, Awang Ngah; Abrizah, Abdullah; Hilmi, M.R. (2009)
The paper describes an exploratory needs analysis for a digital library of Malay manuscripts. The manuscripts are facing several problems, including (a) the lack of trained manu script librarians; (b) budgetary constraints in manual and digital preservation initiatives; (c) the problems in storage and maintenance of the collection; (d) restricted access for users, (e) the need to preserve the fragile manuscripts, (e) the difficulty of undertaking collaborative transliteration work because of the access problems; (f) the dispersal of titles at several repositories which exacerbates the access issue; and (g) a lack of detail in the description in the manuscript library catalogues. The objectives of this study are: (a) to find out the current state of manuscript collection management and practices in selected libraries; (b) to identify the problems faced by manuscript repositories; (c) to study the meta data schema used by repositories to describe their manu script collections, and (d) to identify a suitable open source digital library software to support a digital library of manu scripts. The study gathers qualitative data from an open-ended questionnaire distributed to five manuscript librarians in Malaysia. Cataloguing practices in manuscript repositories were observed and the open-source digital library software Green stone was studied for its suitability. The information gathered and observed which helped determine the requirements of a digital library that empowers repositories in building, storing, preserving and disseminating information about manuscript collections is presented. The design and modules of the digital library are described.